A novel estimator of earth's curvature (allowing for inference as well) - David R. Bell; Olivier Ledoit; Michael Wolf (University of Zurich, Department of Economics, 2023)
This paper estimates the curvature of the Earth, defined as one over its radius, without using any physics. The orthodox model is that the Earth is nearly spherical with a curvature of Û/20, 000 km. By contrast, the heterodox flat-Earth model stipulates a curvature of zero. Abstracting from the well-worn arguments for and against both models, rebuttals and counter-rebuttals ad infinitum, we propose a novel statistical methodology based on verifiable flight times along regularly scheduled commercial airline routes; this methodology allows for both estimating and making inference for the curvature. In particular, a formal hypothesis test resolutely rejects the flat-Earth model, whereas it does not reject the orthodox spherical-Earth model.
Keywords: C12; C13; 330; Flat-Earth model; geodesy; nonlinear least squares; trigonometry